Inhibition effect of polyvinyl chloride on ferrihydrite reduction and electrochemical activities of Geobacter metallireducens. (7th November 2019) - Li, Jiajia; Liu, Fanghua; Yang, Cuiyun; Zheng, Shiling; Xiao, Leilei; Li, Jinhua; Tu, Chen; Luo, Yongming
Abstract: Geobacter metallireducens GS15, a model of dissimilatory iron‐reducing bacteria, is the key regulator in biogeochemical iron cycling. How the emerging contaminant microplastics involved in the iron cycling are driven by microbes on the microscale remains unknown. Hence, the influences of two typical microplastics, polybutylene terephthalate‐hexane acid (PBAT) and polyvinyl chloride (PVC), were explored on the activity of G. metallireducens GS15 with ferrihydrite or ferric citrate as the respective electron acceptors. The results showed that the iron (II) contents in PBAT‐ and PVC‐treatment groups were 16.79 and 6.81 mM, respectively, at the end of the experiment. Compared with the PBAT‐treatment group, scanning electron microscopy and energy dispersive spectrometery revealed that merely a small amount of iron‐containing products covered the surface of PVC. Moreover, PBAT and PVC could both retard the electroactivity of G. metallireducens GS15 at the beginning of microbial fuel cell operation. On the basis of the results above, microplastic PVC might exhibit potential inhibition of the iron cycling process driven by G. metallireducens GS15 with ferrihydrite as the terminal electron acceptor. This study extended our understanding of the influence of the microplastics PBAT and PVC on microbially mediated biogeochemical iron cycling. The findings might have an important implication on the biogeochemical elements cycling in the ecosystem with the involvement of emerging contaminant microplastics.